The Development of Public Relations Media Utilizing Augmented Reality Technology to Enhance Thai Cultural Tourism Along the Bang Yai Canal in the Bang Yai District of Nonthaburi Province - Tongchum, Pratchaya; Sompuet, Preeya (Ratchaphruek Journal, 2026)
This study aimed to: 1) explore the context and readiness of cultural tourism attractions along the Bang Yai Canal, 2) design and develop public relations media using augmented reality technology, and 3) evaluate the effectiveness and satisfaction with the developed media. A mixed-methods approach was employed, with data collected through interviews with five community members, assessments by three experts, and questionnaires administered to 200 tourists. Data were analyzed using descriptive statistics and content analysis. The findings indicated that the Bang Yai Canal area possesses considerable potential in terms of history, culture, and local way of life, particularly at Bang Khulad Market, Wat Ton Chueak, and Chao Pho Jui Shrine. Although basic facilities are adequate, accessibility for the elderly and people with disabilities remains limited, and systematic public relations media are still lacking. The developed media consisted of posters, postcards, and video clips displayed via the Artivive application, covering seven major tourist sites. Expert evaluations revealed that the media were of high quality, especially in terms of design. Tourist satisfaction was at the highest level, with video clips receiving particularly positive responses as they effectively met the expectations of digital-era tourists.